2019
DOI: 10.1590/0004-282x20190149
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer's disease and sleep disturbances: a review

Abstract: The association between Alzheimer's disease (AD) and sleep disturbances has received increasing scientific attention in the last decades. However, little is known about the impact of sleep and its disturbances on the development of preclinical AD stages, such as mild cognitive impairment. This review describes the evolution of knowledge about the potential bidirectional relationships between AD and sleep disturbances exploring recent large prospective studies and meta-analyses and studies of the possible mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 61 publications
0
32
0
1
Order By: Relevance
“…Furthermore, this region is a known epileptogenic zone (33). Our experiments highlight the importance of the cingulate cortex and the consequences of its vulnerability in early AD at the cell-, network- and behavior level (34, 35).…”
Section: Discussionmentioning
confidence: 80%
“…Furthermore, this region is a known epileptogenic zone (33). Our experiments highlight the importance of the cingulate cortex and the consequences of its vulnerability in early AD at the cell-, network- and behavior level (34, 35).…”
Section: Discussionmentioning
confidence: 80%
“…Sleep disturbances are common in Alzheimer's disease, in elderly people and in depression [96][97][98][99]. There is no convincing evidence that sleep disturbances cause Alzheimer's disease.…”
Section: Depression Sleep and Alzheimer's Diseasementioning
confidence: 99%
“…Even with "normal" aging mechanisms, PSG reveals a decrease in slow-wave sleep (SWS), delta-power, sleep efficiency (SE), and an increase in comorbid sleep disorders such as sleep-disordered breathing and periodic limb movements of sleep [17]. The added alterations of neuronal structure in AD can further exacerbate sleep disruption, resulting in an amplified worsening of sleep parameters already seen in aging [18]. Behavioral observations of sleep in an AD special care unit observed that this worsening of sleep was associated with the severity of dementia [19].…”
Section: Overviewmentioning
confidence: 99%